Enhancing ALS disease management: exploring integrated user value through online communities evidence - Hruška, Jan; Bachmann, Pavel; Odei, Samuel Amponsah (Frontiers in Neurology, 2025)
IntroductionAssistive technologies (ATs) offer significant potential to improve the quality of life for individuals with Amyotrophic Lateral Sclerosis (ALS). This study explores the concept of integrated user value (IUV), focusing on five key aspects: quality, user experience, cost-effectiveness, safety, and accessibility. Understanding IUV is crucial for enhancing the development and deployment of ATs in ALS disease management.MethodsA systematic search approach was utilized to collect data from Facebook ALS support groups, comprising posts from individuals with ALS and their caregivers. Using a predefined set of keywords, 416 posts were analyzed. The posts were categorized based on the five aspects of IUV, and an in-depth content analysis was conducted to explore patterns, challenges, and experiences associated with AT usage.ResultsThe analysis revealed significant challenges across all aspects of IUV. Quality and user experience were interlinked, with users frequently citing inadequate designs and unmet customization needs. Cost-effectiveness was a key concern, with high costs and limited insurance coverage contributing to financial strain. Accessibility issues, including delays in acquiring devices and insufficient public facilities, further highlighted systemic challenges. Safety concerns emphasized the need for personalized and intuitive AT designs.DiscussionThe findings underscore the importance of a holistic approach to AT development, integrating all five aspects of IUV. Recommendations include enhancing product quality, ensuring affordability, prioritizing user-centered design, and addressing accessibility gaps. Collaboration between AT designers, healthcare providers, and policymakers is essential to optimize AT value and improve the quality of life for individuals with ALS and their caregivers.